Differential cross section for w boson production as a function of transverse momentum in p p̄ collisions at √s = 1.8 TeV - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alves, G; Amos, N; et al. (2001)
We report a measurement of the differential cross section for W boson production as a function of its transverse momentum in proton-antiproton collisions at √s = 1.8 TeV. The data were collected by the DØ experiment at the Fermilab Tevatron Collider during 1994-1995 and correspond to an integrated luminosity of 85 pb-1. The results are in good agreement with quantum chromodynamics over the entire range of transverse momentum. © 2001 Elsevier Science B.V.